Measurement of ordinary heterotroph organism anoxic yield in anoxic-aerobic activated sludge systems - Muller, Ashley (Department of Civil Engineering, 2017)
The principal aim in this research is to investigate and quantify the ordinary heterotrophic organism (OHO) cell yield under anoxic conditions relative to its value under aerobic conditions for municipal sewage. In this regard, three primary objectives were identified: 1. Determine the ratio Y H,No: Y H,AE for real sewage in terms of electron acceptor (i.e. nitrate and oxygen respectively) utilization. 2. Measure Y H,NO and Y H,AE directly for known concentrations of readily biodegradable (RB)COD utilized. 3. Compare experimental results with other, independent studies on real sewage.